2015
DOI: 10.4283/jmag.2015.20.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Electromotive Force Characteristics for Electromagnetic Energy Harvester using Ferrofluid

Abstract: This paper investigates the concept and implementation of an energy harvesting device using a ferrofluid sloshing movement to generate an electromotive force (EMF). Ferrofluids are often applied to energy harvesting devices because they have both magnetic properties and fluidity, and they behave similarly to a soft ferromagnetic substance. In addition, a ferrofluid can change its shape freely and generate an EMF from small vibrations. The existing energy harvesting techniques, for example those using piezoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Subsequently, an electric current was induced within the inductive coil wrapped around the container generating approximately 1 mW of power. Similar experiments were carried out by Purohit et al [11], Oh et al [12], and Kim [13], generating 9 mV open circuit voltage at 5 Hz vibration frequency. Oh's work also concluded that using an iron yoke around the magnets increased the electromagnetic field (EMF) efficiency.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Subsequently, an electric current was induced within the inductive coil wrapped around the container generating approximately 1 mW of power. Similar experiments were carried out by Purohit et al [11], Oh et al [12], and Kim [13], generating 9 mV open circuit voltage at 5 Hz vibration frequency. Oh's work also concluded that using an iron yoke around the magnets increased the electromagnetic field (EMF) efficiency.…”
Section: Introductionsupporting
confidence: 69%
“…Table 1 compares previously reported energy harvesting devices based on their maximum voltage and maximum frequency. Most devices operate below 10 Hz [ 10 , 13 , 15 , 18 ] with voltages between 9–31 mV. On the other hand, generators that operate at a frequency of 30 Hz tend to have a voltage of around 1 mV showing an inverse relationship between voltage and frequency for this type of liquid energy harvesting device.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of energy using magnetic field was observed by inducing Electro motive Force (emf) in a coil due to oscillat ing nature of the magnetic nanoparticles in ferrofluid [11]. Ferro flu ids are colloidal liquids made up of nanoscale permanent magnetic dipoles, can change shape freely and has ability to generate an electro motive force (emf) fro m s mall v ibrations.…”
Section: Introductionmentioning
confidence: 99%